Non-Target Site Resistance in Summer-Emerging Lolium rigidum and the Effect of Alternative Herbicides - Michael Thompson; Bhagirath S. Chauhan (Agronomy, 2023)
Herbicide resistance is an important weed management issue. Glyphosate is the most dominant herbicide, which controls a broad spectrum of weeds, including grasses such as Lolium rigidum. Lolium rigidum is a major weed of winter crops in Australia that is developing glyphosate resistance in increasing numbers of populations and has been observed growing throughout summer in recent years. Three L. rigidum populations, one summer-emerging glyphosate-resistant (GR), one winter-emerging glyphosate-susceptible (GS), and one winter-emerging population with unknown resistance status (CC04), were analyzed for target-site resistance to glyphosate after confirming their resistance or susceptibility to glyphosate in a dose–response experiment. Population GR was obtained from plants that emerged in summer and contained plants that survived all rates of glyphosate applied (0 to 4560 g a.e. ha−1). It was found to be 6.1 and 4.4 times more resistant than population GS across two experiments. Population CC04 was identified as susceptible. Plants from each population were analyzed for the presence of target-site mutations in the conserved region of the EPSPS gene; however, no mutations were identified that could cause resistance, suggesting non-target-site resistance in population GR. The effectiveness of alternative herbicides was also analyzed for each population. Paraquat was the most effective herbicide, with 0% survival across all populations. The ACCase-inhibiting herbicide clethodim was also highly effective (0 to 8% survival across populations). Other ACCase-inhibiting herbicides, propaquizafop, haloxyfop, and pinoxaden, were effective at controlling the two susceptible populations, CC04 and GS (0 to 36% and 0 to 20% survival, respectively), but were only moderately effective for controlling GR (28 to 51% survival). Paraquat and clethodim may be alternative options for controlling GR populations of L. rigidum and could be effective for use in management programs to slow the development of GR populations.